Double Certificates as Land Administration Defects: Parameters for Cancellation According to Government Regulation 18/2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/2020 and Their Legal Consequences - Sarah Atikasari; Suhadi Suhadi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This article discusses double/overlapping certificates as land administration defects and examines the parameters for their cancellation according to Government Regulation 18/2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/2020, while also testing how these parameters actually work in practice and court decisions. The objectives of this study are (1) to systematize the normative parameters for the cancellation of duplicate certificates as a